Prediction of filter expansion during backwashing - AKGİRAY, ÖMER (IWA PUBLISHING, 2004)
The application of the Ergun equation to predict the expansion of filter media during backwashing is investigated. Fluidization data from the literature have been analyzed and the values k(1) =3.519 and k(2) =0.266 have been found to give a very good fit to the data in the range of Reynolds numbers of interest in filter backwashing. An empirical equation that is applicable over a wider range of Reynolds numbers than the Ergun, equation is also developed. New experiments have been carried out,with glass spheres, plastic. spheres, silica sand, and crushed glass. The effect of particle shape on expansion behaviour is investigated. It is found that the influence of particle shape is larger than previously recognized. Furthermore, the shape effect depends on the Reynolds number based on the backwash velocity. The advantages, limitations, and range of applicability of each method of calculation are delineated.
Keywords: backwash hydraulics; filter backwash; filter media; filtration; fluidization; water treatment; FLUIDIZATION; MEDIA